Developmental trajectories of marital happiness in continuously married individuals: a group-based modeling approach - Anderson, Jared R.; Van Ryzin, Mark J.; Doherty, William J. (My University, 2013)
Most contemporary studies of change in marital quality over time have used growth curve modeling to describe continuously declining mean curves. However, there is some evidence that different trajectories of marital quality exist for different sub-populations. Group-based trajectory modeling provides the opportunity to conduct an empirical investigation of the variance in marital quality trajectories. We applied this method to analyze data from continuously married individuals from the Marital Instability over the Life Course Study (N = 706). Instead of a single continuously declining trajectory of marital happiness, we found 5 distinct trajectories. Nearly two thirds of participants reported high and stable levels of happiness over time, and the other one third showed either a pattern of continuous low happiness, low happiness that subsequently declined, or a curvilinear pattern of high happiness, decline, and recovery. Marital problems, time spent in shared activities, and (to a lesser degree) economic hardship were able to distinguish trajectory group membership. Our results suggest that marital happiness may have multiple distinct trajectories across reasonably diverse populations. Implications for theory, research, and practice are discussed.
Keywords: Developmental trajectories; Group-based modeling; Marital happiness; Time spent in shared activities; Marital problems; Perceived economic distress